International collaboration and comparative research on ocean top predators under CLIOTOP. (June 2017) - Hobday, Alistair J.; Arrizabalaga, Haritz; Evans, Karen; Scales, Kylie L.; Senina, Inna; Weng, Kevin C.
Abstract: Oceanic top predators have ecological, social and economic value of global significance. These wide-ranging marine species, which include sharks, tunas and billfishes, marine mammals, turtles and seabirds, are the focus of international research attention under the Climate Impacts on Oceanic Top Predators (CLIOTOP) science programme, one of the Integrated Marine Biosphere Research (IMBeR) projects. Over more than a decade, research conducted under CLIOTOP has involved scientists from more than 30 countries, with international collaboration increasing markedly over time, and comparative analyses resulting in new knowledge and understanding of oceanic top predators. This special issue presents 27 papers arising from the 3rd CLIOTOP symposium, held in San Sebastián, Spain in September 2015, spanning topics such as conservation biology, trophic ecology, fisheries science, climate change, and adaptive management. The maturation and synthesis of CLIOTOP's collaborative research is now resulting in real-world management applications and improving understanding of potential ecological and socio-economic impacts of climate change in oceanic systems. The ultimate CLIOTOP goal of preparing both climate-sensitive predator populations and the human societies dependent on them for the impending impacts of climate change is now within reach.